The Difference In Breastmilk Production Between Acupresure Point For Lactation And Oxytocin Massage - Rahayu, Dwi; Santoso, Budi; Yunitasari, Esti (Jurnal NERS, 2015)
Introduction: Breastfeeding is the adaptation process experienced by postpartum mothers. If she has assisted carlier in breastfeeding, the mothers will succeed to continue breastfeeding. In reality milk ejection very little on the fi rst daysafter birth is a constraint in early breastfeeding. Acupressure points for lactation can increase milk production, help maximize prolactin and oxytocin receptors and minimize the side effects of delaying in the breastfeeding process. The objective of this study was to prove the difference effect of Acupressure Points for lactation and oxytocin massage to increase milk production and comfort on postpartum mothers. Method: This study used a quasy-experiment design with pre-post test design with control group. The sample of this study was recruited using consecutive sampling, consist of 27 mother postpartum primiparous, divided into 3 groups. Comfort was measured with GCQ, and milk production measured with Weighing Test. Data measured before and after the intervention, and analyzed by ANOVA with Î± = 0.05.Results: The results showed there was a signifi cant difference in comfort between the Acupressure Points for Lactation, oxytocin massage and control group (p = 0.035). and there was a a signifi cant difference in milk production between the Acupressure Points for Lactation, oxytocin massage and Control group (p = 0013). Analysis and Discussion: Conclusion, Acupressure Points for Lactation effective to increase comfort and milk production in postpartum mothers in Kediri District Hospital. This technique should be used as an alternative intervention in treatment of postpartum mothers. Nurses need to teach these techniques to postpartum mothers to be more independent in reduxing the problem of lactation.Keywords: acupressure points for lactation, comfort, Milk Production